Implementasi Metode The Unified Process Pada Mobile Application Monitoring Gizi Bayi Dibawah Dua Tahun - Hartawan, Muhammad Syarif; Nursyanti, Reni (Universitas Muhammadiyah Magelang, 2023)
This study is based on the trend of the nutritional status of Indonesian toddlers which is still unfavorable. In 2021, 24.4% of children under five were stunted, 7.1% were wasted, 17.0% were underweight and 3.5% were overweight. Although in 2022 stunting and overweight decreased to 21.6% and 3.5%, wasting and underweight increased to 7.7% and 17.1%. In addition, there are still many children whose daily needs are not fulfilled, therefore the application of The Unified Process method is used to build a nutrition monitoring application for infants under two years or abbreviated as Baduta. Furthermore, the purpose of the study is the development of a clown child nutrition monitoring application which is expected to help parents, especially those who have babies under two years old, so that they can monitor the development of their child's nutritional intake every day. based on the results of black box testing, it can be concluded that this application is good enough and informative based on providing nutritional information for baduta.